Subversivos : ditadura, controle social e educação superior no Brasil (1964-1988) - Mansan, Jaime Valim (2014)
After the 1964 coup, a peculiar system of social control was set up in Brazil to ensure the success of that dictatorial political project and the maintenance of that social order. This system remained active until 1988, passing, however, through a series of transformations over the period. Its performance on the field of higher education reveals certain specificities. Four modes of control (surveillance, repression, propaganda and formation of intellectuals) are analyzed with an emphasis on the relations among themselves, as well as on targets, structures, methods and functions of each one of them. The four modes were based on the notion of subversion with significant influence of the National Security Doctrine produced by the Escola Superior de Guerra (war college) and other sources (such as anti-communist imaginary). For repression and surveillance processes, several organs of these two structures of control are examined , such as Departamentos de Ordem Política e Social (political police), Polícia Federal (federal police), military intelligence agencies (Centro de Informações do Exército, Centro de Informações de Segurança da Aeronáutica, Centro de Informações da Marinha and Segundas Seções), Serviço Nacional de Informações (intelligence agency), paramilitary groups, Operação Bandeirante and the DOI/CODI system (political police), Ministério da Educação e Cultura (Ministry of Education and Culture) and some subordinate offices (Comissão de Investigação Sumária, Divisão de Segurança e Informações, Assessorias [Especiais] de Segurança e Informações) as well as the cooperation of deans and other agents in the field of higher education. Boletins Diários à Imprensa (daily bulletins sent to press) and three newsreels (Informativo, Atualidades and Brasil Hoje), all produced by Agência Nacional, are used for analysis of social control through propaganda. To study the formation of pro-regime intellectuals and social support, it s especially evaluated the contributions of Escola Superior de Guerra (ESG), Associação dos Diplomados da Escola Superior de Guerra (ESG alumni association) and moral and civic education at the undergraduate and graduate level (Estudos de Problemas Brasileiros discipline).